The Impact of Resource Optimization on the Economic Development of the Marine Industry - Tingting Wang; Xiulian Yang (Discrete Dynamics in Nature and Society)
The traditional impact analysis method for the economic development of marine industries does not consider the impact weight of different marine industries, which leads to an unsatisfactory effect on sustainable development after the optimized management of resources. Therefore, a new method is designed to solve the above problems; by analyzing the scale, hierarchical system, and optimizing the spatial resource framework of the marine industry, the influence of different marine industries is comprehensively measured, and the final demand dependency of the marine industry economy is obtained. The comprehensive index system is designed to evaluate the economic development of the marine industry, and the linear weighted sum method is used to calculate the sustainable development degree of marine industry economy in different regions. The results show that the final evaluation score of the marine biological industry in Shandong Province is 64.97, which is affected by comprehensive factors. The scores of capital and environmental governance are between 84.03 and 82.87, respectively, which are the main factors to achieve sustainable development. After the optimization of this method, the demand dependence of relevant regions is reduced, and the sustainable development level is effectively improved, indicating that the sustainable state of this method is better. The resource optimization path given by the research can be further applied to the construction process of marine and industrial economic development in other provinces and cities so as to comprehensively improve the quality and effect of marine economic growth.